Biofunctionalization of titanium implants with a biomimetic active peptide (P-15) promotes early osseointegration - Lutz, Rainer; Srour, S.; Nonhoff, J.; Weisel, T.; Damien, C. J.; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2010)
Objectives: The early stages of peri-implant bone formation play an essential role in the osseointegration and long-term success of dental implants. By incorporating bioactive coatings, this biofunctionalization of implant surfaces may enhance the attachment of the implant to the surrounding bone and stimulate bone regeneration. Material and methods: To demonstrate faster osseointegration, the surfaces of dental implants were grit-blasted and acid-etched. They were then coated with hydroxyapatite (HA) and experimental implants were further coated with a biomimetic active peptide (P-15) in one of two concentrations. These biofunctionalized samples and controls with no peptide were placed in the forehead region of 12 adult pigs. Six animals were evaluated for a period of 14 or 30 days. Results: Histomorphometric analysis demonstrated that the implants with the high concentration of P-15 had significantly higher percentage of bone-to-implant contact (BIC) at 14 (P=0.018) and 30 (P=0.015) days compared with the other groups. Both concentrations of P-15 showed increased peri-implant bone density compared to the control group at 30 days. Conclusion: Biofunctionalization of the implant surface with a biomimetic active peptide leads to significantly increased BIC rates at 14 and 30 days and higher peri-implant bone density at 30 days.© 2010 John Wiley and Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Animal experiments; Biomaterials; Bone implant interactions; Bone regeneration; Guided tissue regeneration